Temperature dependence of water cluster on functionalized graphite. (15th October 2021) - Horikawa, Toshihide; Yuasa, Ryuto; Yoshida, Ken; Do, D.D.
Abstract: Our recent experimental study of water adsorption in micro-mesoporous carbons at 263 K and 298 K show an unusual temperature dependence of adsorbed density with higher loading at 298 K at the same reduced pressure. The difference is in the filling of mesopore at 298 K and its absence at 263 K, and it was conjectured to the growth of water clusters on the functional groups in the confined space of mesopores in which the water clusters at 298 K are sufficiently large to induce the subsequent filling. Since the growth of these clusters and their coalescence is the prerequisite for filling, the filling is absent at 263 K simply because of the smaller size of the clusters, preventing them from coalescence and hence, no filling. In a quest to understand the effects of temperature on water adsorption in micro-mesoporous carbon, we used molecular dynamic simulation to reveal the mechanism of water adsorption around functional groups from 263 K to 328 K to clarify the growth of the water cluster as a function of temperature. The results clearly show that the water cluster is larger at 298 K compared to 263 K, confirming the conjecture from our previous works. Graphical abstract: Image 1 Highlights: Water cluster on a functional group dynamically interchanges its configuration between a string and a ring structures. The size of water cluster is a complex function of temperature. MD simulation of water adsorption sheds insight into the mechanism of the water cluster formation at different temperatures. The unusual temperature dependence of the water adsorption isotherm is related to the cluster size. Stability of water cluster is better with carboxy than hydroxy group.